Gait Initiation in Parkinson’s Disease: Impact of Dopamine Depletion and Initial Stance Condition - Palmisano, Chiara; Brandt, Gregor; Vissani, Matteo; Pozzi, Nicoló G.; Canessa, Andrea; Brumberg, Joachim; Marotta, Giorgio; Volkmann, Jens; Mazzoni, Alberto; Pezzoli, Gianni; Frigo, Carlo A.; Isaias, Ioannis U. (Frontiers in Bioengineering and Biotechnology, 2020)
Postural instability, in particular at gait initiation, and resulting falls are a major determinant of poor quality of life in subjects with Parkinson’s disease (PD). Still, the contribution of the basal ganglia and dopamine on the feedforward postural control associated with this motor task is poorly known. In addition, the influence of anthropometric measures and initial stance condition on gait initiation has never been consistently assessed. The biomechanical resultants of anticipatory postural adjustments contributing to gait initiation (imbalance, unloading and stepping phase) were studied in 26 unmedicated subjects with idiopathic PD and in 27 healthy subjects. A subset of 13 patients was analysed under standardized medication conditions and the striatal dopaminergic innervation was studied in 22 patients using FP-CIT and SPECT. People with PD showed a significant reduction in center of pressure displacement and velocity during the imbalance phase, reduced first step length and velocity, and decreased velocity and acceleration of the center of mass at toe off of the stance foot. All these measurements correlated with the dopaminergic innervation of the putamen and substantially improved with levodopa. These results were not influenced by anthropometric parameters or by the initial stance condition. In contrast, most of the measurements of the unloading phase were influenced by the foot placement and did not correlate with putaminal dopaminergic innervation. Our results suggest a significant role of dopamine and the putamen particularly in the elaboration of the imbalance phase of anticipatory postural adjustments and in the execution of the first step. The basal ganglia circuitry may contribute to defining the optimal referent body configuration for a proper initiation of gait and possibly gait adaptation to the environment.